Presentation. Polyphonies of the Indomitable: New Literary Studies of Gender and Sexualities - Fernández Pérez-Sanjulián, Carme (Madrygal. Revista de Estudios Gallegos, 2025)
This article presents the monograph Polyphonies of the Indomitable: New Literary Studies of Gender and Sexualities, which emerged from an academic dialogue initiated at the conference “Saberes en alianza” (University of A Coruña, May 2025). The volume brings together a carefully selected set of original contributions that combine theoretical reflections on gender, sexuality, nation, and canon with case studies focused on erotic poetry and contemporary dystopian narrative. Taken as a whole, these contributions propose new critical approaches that place bodies, subjectivities, and sexo-affective relations at the centre of current Galician literary studies.